A Note on Recent Developments in the Theory of Elastic Plates with Moderate Thickness - Lewiński, T. (Engineering Transactions, 1986)
The paper refers to Reddy’s concept (Int. J. Solids Struct., 20, No 9/10, pp. 881-896, 1984) of a construction of the energy consistent theory for plates with moderate thickness; this theory is based on the kinematical hypothesis known from the monographs by Ambartsumian and Kączkowski. With the use of other. independent physical quantities. (we handle the averaged Reissner’s rotations), the equations of motion and boundary conditions are derived. By means of simplifications of functionals, the governing equations and boundary conditions of the Reissner-type model (found by Kączkowski and then discovered again by Levinson) are arrived at. In the last section a proof is given that there is no simple generalization of the kinematical hypothesis used in the paper which would lead to an energy-consistent and physically correct theory of the Reissner class.